KUALITAS PELAYANAN DI SISI BARAT COFFEE BOGOR: - Sutardi, Heri; Arrahman, Zannu (JURNAL PARIWISATA VOKASI, 2023)
In this research, the focus is on the quality of restaurant waiter service on the West Side of Coffee Bogor. Where good service quality is very important to produce employee performance and create a good hotel image. This research aims to: a.) How is the physical evidence seen at West Side Coffee Bogor? b.) How is the reliability of employees at West Side Coffee Bogor? c.) How is the responsiveness of employees at West Side Coffee Bogor? d.) What is Has the guarantee made by employees at West Side Coffee Bogor been implemented? e.) Is there concern from employees towards guests at West Side Coffee Bogor? The method applied in preparing this Final Assignment is Descriptive.